2010
DOI: 10.1016/j.jad.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of emotion on cognition in trauma survivors: What is the role of posttraumatic stress disorder?

Abstract: Background: Cognitive theories of anxiety disorders postulate an increased attentional bias to environmental cues associated with threat that underlies the exaggerated fear response. The role of trauma, which may represent strong competitive advantage for attention, remains unclear. We investigated the influence of trauma exposure and the presence of anxiety/stress disorders on the impact of emotional distractors on cognitive performance. Methods:Fourteen trauma-exposed subjects with PTSD, 12 trauma-exposed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…This is consistent with prior research with the AS in which negative and positive trials are typically analyzed separately (Blair et al, 2007; Vythilingam et al, 2007; Mueller-Pfeiffer et al, 2010). During each number trial, participants viewed a central fixation point, a first numerical display, a picture display, a second number display, and a second picture display of 400ms each, ending in a blank stimulus of 1000ms (Figure 1).…”
Section: Methodssupporting
confidence: 89%
“…This is consistent with prior research with the AS in which negative and positive trials are typically analyzed separately (Blair et al, 2007; Vythilingam et al, 2007; Mueller-Pfeiffer et al, 2010). During each number trial, participants viewed a central fixation point, a first numerical display, a picture display, a second number display, and a second picture display of 400ms each, ending in a blank stimulus of 1000ms (Figure 1).…”
Section: Methodssupporting
confidence: 89%
“…PTSD has repeatedly been associated with attentional biases towards threat and negative emotional stimuli, as exhibited by performance on the modified Stroop (Williams , et al 1996), which involves timed verbalization regarding the ink color of emotional and neutral words(Mathews and MacLeod 1985), and dot-probe tasks(MacLeod , et al 1986), in which targets are displayed in locations closer to previously-presented trauma-relevant, generally negative, or neutral stimuli (Dalgleish , et al 2003; Foa , et al 1991; McNally , et al 1990; Chemtob , et al 1999; Mueller-Pfeiffer , et al 2010; Kimble , et al 2010); except see (Bremner , et al 2004; Kimble , et al 2009). Observed performance differences on these tasks could be due to either attentional facilitation involving enhanced detection of threat-relevant stimuli, or attentional interference involving difficulty disengaging from threat-related stimuli to focus attention on the task at hand.…”
Section: Attention Working Memory and Executive Function In Ptsdmentioning
confidence: 99%
“…Other studies have examined the effect of inserting emotional images into the working memory task as distractors (e.g., directly prior to number Stroop decisions or in between encoding and recall for working memory tasks). Results from these studies have been mixed, with one study reporting PTSD to be associated with worse detectability scores across working memory trials regardless of distractor type (neutral vs. trauma-related) (Morey , et al 2009), while another study reported PTSD patients to exhibit greater response latency for number Stroop after negative (versus positive or neutral) images as compared to trauma-exposed and non-trauma-exposed control groups (Mueller-Pfeiffer , et al 2010). These results suggest that the acute emotional state may not have an overwhelming effect on objective cognitive function in PTSD.…”
Section: Attention Working Memory and Executive Function In Ptsdmentioning
confidence: 99%
“…In the present study, we sought to investigate the effects of YM on emotion-cognition interactions. YMP and a matched control group (CG) of yoga and meditation naïve subjects underwent fMRI scanning while performing an Affective Stroop Task (Blair et al, 2007; Vythilingam et al, 2007; Hasler et al, 2009; Mueller-Pfeiffer et al, 2010; Froeliger et al, 2011, 2012), a modified version of the Number Stroop task (Pansky and Algom, 2002). The Affective Stoop task was designed to evaluate emotional information processing and its effects on cognitive conflict resolution.…”
Section: Introductionmentioning
confidence: 99%